Organization of Promotion of the System of Physical Education in its Institutions - Matchanov Ruslanbek Azatovich (Zien Journals, 2022)
In this scientific research work, it is intended to popularize physical education and sports aimed at health among the population and thereby develop methods that serve to develop the thinking of young people.
Keywords: physical training; technical training; methodology; training process